US policy toward Syria and its attitude on Syrian-Sovietrelations in 1957 - رشيد محمد, اياد; رياض عبد المجيد, لبنى; حمزه حسين, محمد (Journal of College of Education, 2020)
US relations with Arab Middle East countries began remarkably in the 1940s through the interest of American politicians in political developments in the region, particularly in Syria.  Syria has witnessed a wave of military coups that began with the coup of Hosni al-Zaim on March 30, 1949, and how the United States did not oppose this coup as a result of Hosni al-Zaim's commitment to abide by all international commitments and agreements.  Despite some sources, the US government was behind the coupHowever, it seems that the subsequent development of relations was behind this exaggerated impression, Hosni al-Zaim approached the United States through his agreement to the Tabline and his commitment to the fight against communism and conciliation with Israel, which led to the strengthening of his relations with the Americans, and after the coup Sami Hinnawi  The United States has met with a cold-hearted coupAs a result of the proximity of the leaders of this coup to the Kingdom of Iraq supported by Britain and the relentless pursuit of a proposed union that includes Syria and Iraq, and this was rejected by the United States of America for the possible impact on its interests in the region, and Syria in particular.  After the coup of Adib Shishakli, the United States welcomed his establishment and hastened to strengthen relations with the Shishakli regime The US government has worked to link military aid and economic aid to Syria by accepting the resettlement of Palestinian refugees in Syria, improving relations and concluding a permanent peace with Israel. The United States sought to bring the countries of the region, including Syria, into its sphere of influence and control.  That is why the United States has sought to include Syria in its sphere of influence through its projects, including the 1950 Tripartite Declaration, the Middle East Command 1951, and the Baghdad 1955 Pact. After the end of the military coups in 1954 and the advent of national governments in Syria, they felt that a positive neutrality approach serves national goals better than aligning with one of the eastern or western camps, and considered that the United States' biased policy towards Israel without regard to national hopes.  Arabic is a direct threat.  This is why Syria has rejected Western alliance projects, but the US administration has interpreted this as a Syrian bias towards world communism, and this threatens its interests in Syria. It should also be emphasized here the position of the Syrian people who stood against and denounced US allies and projects.As a result of these Syrian national stances against alliances and American projects, the United States decided to exert all pressure and provocations on the Syrian governments in order to get them to accept their projects in the region.  Chief of Staff of the Syrian Army (Maliki) on April 22, 1955 by a member of the Syrian National Social Party and with the support of the CIA in Damascus, despite the denial of the US government of any role in the assassination.  Not only did the US government organize foreign conspiracies in cooperation with neighboring Syria, including Iraq and Turkey. The Eisenhower doctrine in 1957 was a new episode in a series of Western alliances and projects that are at the core of US policy of dominating the Arab region. Syria rejected this project and promised it an alternative to the Baghdad alliance.